Development of Human Resources Quality of Dani Tribe Through Empowerment of Indigenous Communities Integration, Local Wisdom Values and Multicultural Education - Husna, Uswaul; Jam'an, Andi; Jusriadi, Edi (Golden Ratio of Social Science and Education, 2025)
This research can be focused on implementing multicultural education based on local wisdom in supporting the improvement of the quality of human resources of the Dani tribe, and on empowering the Dani tribe in improving the quality of human resources. Objectives: This study aims to determine how implementing multicultural education and empowerment based on local wisdom supports improving the quality of human resources of the Dani tribe. This study uses a qualitative approach to understand in depth how integrating local wisdom values, multicultural education, and empowerment of indigenous tribes improves the quality of human resources of the Dani Tribe in Papua Mountains. The results of this study show that the cooperation system is still strong in various communal activities, such as agriculture and development, which shows the strength of social values that support sustainable development. Implementing multicultural education in the Dani Tribe community has shown positive results in developing human resources. Integrating local cultural values into the formal curriculum has created a more relevant and meaningful education system for students. The empowerment of indigenous communities has developed significantly by combining the development of traditional and modern skills. The decision-making system based on customary deliberation or 'wim' remains an important foundation in the development process. The Dani Tribe community has shown good adaptability in facing modernization. They have successfully integrated modern technology, such as social media, to market traditional products while maintaining cultural values. Adapting educational methods to contemporary needs has also been done without sacrificing the essence of their traditional values.